2020
DOI: 10.3390/ijerph17218202
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Resilience, Sense of Coherence and Coping in People with Multiple Sclerosis in the Situation Derived from COVID-19

Abstract: The confinement forced by COVID-19 can have repercussions on the health of people diagnosed with multiple sclerosis. The objective of this study is to analyze the relationships between physical activity, a sense of coherence, resilience and coping among people diagnosed with Multiple Sclerosis during the health emergency situation. To achieve this goal, this transversal descriptive study included 84 patients that belonged to multiple sclerosis associations during the period of confinement. Participants filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
1
29
2
Order By: Relevance
“…Overall, looking to the variety of coping strategies, the most frequent strategies evaluated as useful in patients' eyes were social support, hobbies, and keeping oneself busy. Results are quite different from what was observed in a previous study where active coping and religion were the strategies most frequently adopted in order to face COVID-19 ( 31 ). Conversely, the relevance of those coping strategies, which emerged in our study, was consistent with other results reported during the COVID-19 pandemic and, more in general, in the chronic disease field, as discussed in the section below.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, looking to the variety of coping strategies, the most frequent strategies evaluated as useful in patients' eyes were social support, hobbies, and keeping oneself busy. Results are quite different from what was observed in a previous study where active coping and religion were the strategies most frequently adopted in order to face COVID-19 ( 31 ). Conversely, the relevance of those coping strategies, which emerged in our study, was consistent with other results reported during the COVID-19 pandemic and, more in general, in the chronic disease field, as discussed in the section below.…”
Section: Discussioncontrasting
confidence: 99%
“…This mean value was found to be 2331.3 ± 3811.9 MET minutes per week in our sample. On the other hand, COVID-19 positive cases were reported to be 1140.8 ± 1428.2 min per week which is almost half the value of negative cases ( Reguera-García et al., 2020 ). These numerical values reveal how much the physical activity levels of COVID-19 positive individuals are highly affected.…”
Section: Discussionmentioning
confidence: 93%
“…The Brief-COPE results showed that the respondents to our survey overall preferred problem-focused coping, with planning, active coping and positive reframing as the most frequently used strategies. In another study, Spanish MS patients, surveyed during the pandemic, favored active confrontation and religion, while their use of emotional support, humor and positive re-evaluation was less frequent than in healthy controls [ 4 ]. The Italian survey [ 13 ] also indicated preference for positive attitude, problem solving and turning to religion among MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Disability and immunocompromised status due to disease-modifying treatment (DMT) were initially considered as predisposing factors for severe course to various forms of therapy and rehabilitation [ 1 , 2 ]. Furthermore, cognitive and mental health problems which often occur in MS population, together with insufficient coping abilities, would make these patients more vulnerable to distress caused by the pandemic [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%